Analisis Mutu Pelayanan Publik dalam Penyaluran Bantuan Sosial oleh Dinas Sosial Kabupaten Kerinci - Utari Tri Wahyuni; Hapsa Hapsa; Fajar Alan Syahrier (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2026)
Public service quality plays a crucial role in ensuring that social assistance is delivered effectively to vulnerable communities. This study aims to analyze the quality of public services in the distribution of social assistance by the Social Service Office of Kerinci Regency and to identify improvement efforts undertaken by the institution. This research employed a descriptive qualitative approach using observation, interviews, and documentation techniques. Informants consisted of Social Service officials, social facilitators, and beneficiary communities. Service quality analysis was conducted using the SERVQUAL dimensions: tangible, reliability, responsiveness, assurance, and empathy. The findings indicate that the social assistance distribution service in Kerinci Regency is generally adequate, particularly in the assurance and empathy dimensions. Beneficiaries feel that services are delivered fairly, transparently, and without discrimination. However, obstacles remain in the tangible, reliability, and responsiveness aspects, including limited service facilities, inaccurate beneficiary data due to incomplete DTKS updates, and delays in assistance distribution in remote areas caused by geographical constraints. To address these challenges, the Social Service Office has implemented periodic data validation, strengthened coordination with village administrations, and optimized digital-based social service information systems. This study provides empirical evidence that can serve as an evaluation reference for local governments in improving transparent, effective, and equitable social assistance services.